Aerosol Delivery of Polyelectrolyte Surfactant—Antimicrobial Nanoparticles to the Lungs - Yadiel Varela Soler; Amanda S. Padilla-López; Sughosha Rao; Leonardo Calderon; Gediminas Mainelis; Olga Garbuzenko; Tamara Minko; David I. Devore; Charles M. Roth (Pharmaceutical Research, 2026)
Background Lung infections affect over 80% of adults with cystic fibrosis, with Pseudomonas aeruginosa being a leading pathogen. Although antibiotics are frequently nebulized as standard treatments, the physicochemical environment of the diseased lung often limits their diffusion and overall effectiveness. Our previous studies showed polyelectrolyte surfactants (PS) to be a promising delivery system for cationic antimicrobials in vitro . This study seeks to expand that knowledge by evaluating their potential for nebulized delivery. Methods To achieve this, we evaluated their size and antimicrobial activity following nebulization; in vitro toxicity against epithelial cells and erythrocytes; and biodistribution and expression of inflammation markers following administration to healthy mice. Results The nanoparticle formulation exhibited a mucolytic effect on an artificial mucus model of cystic fibrosis mucus. Following nebulization, nanoparticles retained both their size and biological activity. Additionally, they displayed no observable toxicity in vitro against either human lung epithelial cells or erythrocytes; instead, epithelial cells treated with PS-based nanoparticles showed increased cell viability. Following administration of these formulations to mice via inhalation, over 70% of the recovered nanoparticles were retained in the lungs 24 h after treatment, with a small fraction being uniformly distributed to other tissues. A screen of key inflammatory cytokines revealed that inhalation treatment led to a slight increase of IL-6 in the liver and IL-18 in the spleen. These increases seem to be consistent with a minor inflammatory response. Conclusion Overall, the results suggest that PS are a promising nanotechnology for the pulmonary delivery of cationic drugs.